Reflections on COVID -19 and the potential impact on preterm infant feeding and speech, language and communication development. Issue 3 (June 2021) - Harding, C.; Aloysius, A.; Bell, N.; Edney, S.; Gordon, Z.; Lewis, H.; Sweeting, M.; Murphy, R.
Abstract: Infants needing the support of a neonatal unit have unique, individual needs that require a Synactive approach to enable effective management of both the environment and the infant themselves (Als, 1986). Parents working in partnership with neonatal colleagues play an essential role in developing competent skills to appraise an infant's function. For parents, learning to care and interact with their infant on a neonatal unit presents unexpected complications including learning to cope and be close to their baby in an unfamiliar setting (Cardin, 2020). The current COVID -19 pandemic has challenged all aspects of neonatal work causing anxiety and stress for all involved in infant care. Neonatal teams have been working together to continue to provide excellent care, and to make adaptations in a difficult and unfamiliar situation. A major change to practice has been the need to limit parent visiting time and access to the cot -side. This is further complicated by the need for practitioner use of face - masks and personal protective equipment when treating infants on neonatal units which has inevitably altered the traditional developmental care approaches undertaken in the UK (Altimier et al., 2015).